Laporan Kasus Asuhan Kebidanan Kehamilan pada Ny. S Umur 25 Tahun G1P0A0 dengan Implementasi Aromaterapi Peppermint pada Ibu Hamil dengan Keluham Emesis Gravidarum: (Puskesmas Melayu Kota Piring, Tanjungpinang, Tahun 2025) - Mulyati Mulyati; Marella Marella; Melly Damayanti; Nurul Aini Suria Saputri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Emesis gravidarum experienced by pregnant women can affect both maternal and fetal health, particularly in terms of nutrition and quality of life. One non-pharmacological approach that can be applied is peppermint aromatherapy, which should be implemented through safe and comprehensive midwifery care tailored to the mother’s needs. This case report aims to evaluate the effectiveness of peppermint aromatherapy in reducing symptoms of emesis gravidarum. The subject is Mrs. S, a 25-year-old pregnant woman at 7–8 weeks of gestation who received care at Melayu Kota Piring Public Health Center, Tanjungpinang, from February to March 2025. Data were collected through interviews, observations, physical and laboratory examinations, and documentation using the SOAP format. The results showed that peppermint aromatherapy effectively reduced the frequency and severity of nausea and vomiting, helping the mother maintain better food intake. In conclusion, peppermint aromatherapy can serve as an effective non-pharmacological alternative for managing emesis gravidarum in primary healthcare settings.